PERSEPSI MAHASISWA TENTANG SEMANTIC SCHOLAR SEBAGAI ALAT BANTU PENCARIAN INORMASI AKDEMIK - Vivi Widya; Rini Asmara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the perception of students of the Library andInformation Science Study Program class of 2021 and 2022 about SemanticScholar as a tool for searching academic information. The theory used in thisstudy is the TAM (Technology Acceptance Model) theory. By using fourindicators, namely easiness, clear and understandable, easy to learn, and overallease. The research method used was qualitative descriptive with a sample of 66students who were selected using the purposive sampling technique. Theresearch uses data collection techniques through the distribution ofquestionnaires. The results of this study show that students perception ofSemantic Scholar as an information search tool is in the good category with anaverage score of 2.51 – 3.25 from a scale of 1 – 4, where the results on the easeindicator are 2.98, clear and understood at 2.92, easy to learn at 3.02, and overallease of 3.06.